PENGARUH MODEL PEMBELAJARAN QUANTUM LEARNING TERHADAP HASIL BELAJAR IPAS PESERTA DIDIK KELAS V SEKOLAH DASAR - Sabila, Cantika; Rabiyatul Adawiyah Siregar; Fadhillah Khairani; Frida Destini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The problem addressed in this study is the low learning outcomes in Natural and Social Sciences (IPAS) among fifth-grade students at SD Negeri 02 Rajabasa Jaya, which is caused by a teacher-centered learning process. This study aims to determine the effect of the Quantum Learning model on the IPAS learning outcomes of fifth-grade elementary school students. This research employed a quantitative approach with a quasi-experimental method using a non-equivalent control group design. The research sample consisted of the entire population, namely 34 students, selected through a non-probability sampling technique with a saturated sampling method. Data were collected through test and non-test techniques, while the data analysis technique used was simple linear regression. The results showed that the implementation of the Quantum Learning model had a positive and significant effect on the IPAS learning outcomes of fifth-grade students at SD Negeri 02 Rajabasa Jaya. This was proven by the results of the simple linear regression test, which obtained a significance value of 0.000 < 0.05 and an R Square value of 62.6%.